VD_FINDINFO Décision / 2013 / 19 vom 26. Dezember 2012 - VD Tribunal cantonal (2012)
MOTIVATION DE LA DÉCISION, DÉTENTION PRÉVENTIVE | 29 al. 2 Cst., 221 CPP (CH), 226 CPP (CH), 393 al. 1 let. c CPP (CH)